Lest we Forget: The Darker Side of the Hypocholesterolemic Statin Drugs - Whitehouse, Michael W; E Butters, Desley (Pharmacognosy Communications)
Cholesterol-lowering statin drugs have been over-sold to the medical pro fession and over-prescribed by physicians, without due concern for their long-term disabling side-effects. These include acute renal failure, devel opment of cataracts, diabetes, liver dysfunction and disabling myopathy. Most were predictable and have been well-documented: yet there has been little reduction in statin usage. The situation is made worse by more recent a) claims for off-label efficacy e.g. as anti-inflammatory agents and b) availability in some countries (e.g. UK) as over-the-counter medications. [1] Is it now time to carefully reconsider the need for such over-prescribing, with the promise of yet more to come (OTC availability, the ‘polypill’)?
Keywords: Statins; Adverse effects; Cholesterol; Coenzyme Q; Dolichol; Polyisoprenoids